More common RNAemia in the early stage of severe SARS-CoV-2 BF.7.14 infections in pediatric patients - Yu Sun; Runan Zhu; Yang Pan; Ri De; Shuang Liu; Liping Jia; Bing Lv; Xiaoyun Li; Dongmei Chen; Yao Yao; Dong Qu; Daitao Zhang; et al. (Elsevier, 2024)
The risk factors of severe infections in children during the severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) outbreak in Beijing remain elusive. SARS-CoV-2-positive children admitted to the intensive care unit (ICU) with collected plasma specimens were enrolled and screened for common pathogens using capillary electrophoresis-based multiplex PCR from December 12, 2022, to January 24, 2023. The SARS-CoV-2 sub-variants were identified using next-generation sequencing. Plasma was positive for two (positive; P), one (suspicious; S), or no (negative; N) SARS-CoV-2 genes were classified as plasmatic RNA-positive (RNAemia; P + S) or without RNAemia (N). Clinical and laboratory data of the enrolled cases were then collected and analyzed. The 34 enrolled children included 26 males and 24 younger than three years. All were negative for other respiratory pathogens. BF.7.14 (18/29) was the predominant subvariant. Viral loads in respiratory specimens, hours from symptom onset to the first respiratory specimen collection (time-variable), with comorbidities and BF.7.14 and BA.5.2 distributions were significantly different in P vs. N and RNAemia vs. without RNAemia group. Among most cases, the T lymphocyte ratios decreased, while the cytokine level and the B lymphocyte ratio increased. The time variables were 2.22 ± 2.05 and 4.00 ± 2.49 days in BF.7.14 and BA.5.2 infections, respectively. In conclusion, SARS-CoV-2 was more likely to cause severe infections among males aged ≤ 3 years old with comorbidities during the SARS-CoV-2 outbreak in Beijing, while RNAemia is more common in children at the early stage of severe BF.7.14 infections, and most had high cytokine levels and B-cell activation.